AB0714 Differentiating characteristics in patients with spondyloarthritis who have received differents anti-tnf therapies. (15th June 2017) - Moral, E; Plasencia, C; Salcedo, D Pascual; Tornero, C; Bogas, P; Navarro, V; Villalba, A; Peiteado, D; Monjo, I; Balsa, A
Abstract : Background: The term spondyloarthritis (SpA) encompass a group of crhonic inflammatory disease with predominant axial involvement. Anti-TNF therapy (AT) has stirred up the management of these diseases. Nevertheles, according to nationwide registries of the drug continuation rate in several countries, the rate of treatment failure is considerable. Nowdays there are insufficient data to evaluate the differences between responders (Resp-AT) and non-responders (Nonresp-AT) to anti-TNF therapy. Objectives: To compare the main sociodemographic, clinical and analytical features at baseline, after 6 months of treatment and at the end of the first anti-TNF therapy of responders to a first anti-TNF therapy and non-responders to several anti-TNF therapies form our cohort of patients diagnosed with SpA. We also analized the association between drug levels (DL) and antidrug antibody (ADA) in non-responders to several anti-TNF. Methods: 181 patients were included, 155 (85%) kept receiving their first AT therapy (responders) and 26 (15%) had discontinued at least two different AT therapies. The main demographic features, disease activity (BASDAI, ASDAS, CRP and ESR) were measured at baseline, after 6 months (v-6) and when the first AT was discontinued. Serum drug levels and/or ADA were measured at drug discontinuation of anti-TNF treatment and last visit in non-responders and responders respectively. Results: The mean age was 55.3±15 and 50±10.8 in the resp-AT and nonresp-AT groups, respectively. The demographic and clinical characteristics of both groups are shown in Table 1 . At baseline, a lower BMI was observed in the resp-AT group (25.6±5 resp-AT, 28.7±5 nonresp-AT, p=0.013); 59% and 35% were in concomitant treatment with DMARDS at baseline in the resp-AT and nonresp-AT groups respectively (p=0.032); 33% of the resp-AT were in monotherapy in the last visit compared to 62% of the nonresp-AT when discontinued the 1st AT (p=0.008). There were no differences in BASDAI (5.6±2 resp-AT, 6.1±1.9 nonresp-AT, p=0.2) and ASDAS (3.3±1.1 resp-AT, 3.4±1.1 nonresp-AT, p=0.8) at baseline. In v-6, the resp-AT group had a better clinical response in terms of BASDAI (3.2±2.3 in resp-AT, 4.7±2.4 in nonresp-AT, p=0.004) and ASDAS (1.7±0.9 in resp-AT, 2.7±1.2 in nonresp-AT, p=0.00), as well as in the delta-ASDAS (ΔASDAS) (1.56±1.2 resp -AT, 0.7±0.9 nonresp-AT, p=0.04). However, delta-BASDAI (ΔBASDAI) showed no difference between the two groups (2.3±2.3 resp-AT, 1.5±1.6 nonresp-AT, p=0.1). 24% of the nonresp-AT were ADA + at drug discontinuation, while only 0.7% of the AT-resp (AT) were ADA + (p=0.00) at last visit. Conclusions: In our cohort of patients with axial SpA, a significant improvement in BASDAI, ASDAS and ΔASDAS after 6 months of treatment is associated with a lower frequency of drop-out of the first AT. Moreover a lower BMI, DMARDS at baseline and absence of ADA determine a better response to AT treatment. Disclosure of Interest: None declared